CREATING A WEB APPLICATION FOR VIEWING DIGITAL MAP DATA AND DISPLAY EXTERNAL DATA FROM APRS (Perner's Contacts, 2015)
The following text describes how to create a Web application to view digital maps with the ability to import external data, which should basically be used for display and analysis of data indicative of the position of APRS (Automatic Packet Reporting System) to the off-line map.
Keywords: online map, ARPS, routes, position